Pengaruh Disiplin Kerja, Tunjangan Kerja, dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Aparatur Kabupaten Tulungagung - Medice Medice; Deby Satyo Rusandy (Otonomi, 2023)
The aim of the research is to determine the influence of Work Discipline, Work Allowances and Work Motivation on Employee Performance at the Personnel Agency and Human Resources Development of Tulungagung Regency Apparatur ,The research results show that the R square value or coefficient of determination (KD) shows how good the regression model is formed by the interaction of the independent variable and the dependent variable. The KD value shows 53.9% so it is interpreted that variables X1, The results of the F test and t test of the variables Work Discipline (X1), Work Motivation (X2), Work Benefits (X3), have a significant positive effect on employee performance.